The Relationship Between Child Maltreatment and Dispositional Envy and the Mediating Effect of Self-Esteem and Social Support in Young Adults - Xiang, Yanhui; Wang, Weixin; Guan, Fang (Frontiers in Psychology, 2018)
As child maltreatment is a common social problem worldwide, the present study explores the relationship between child maltreatment and dispositional envy and the mediating effects of self-esteem and social support in this relationship. Data were collected from 426 Chinese college students (M age = 20.63, SD = 1.85), using the Child Abuse Scale, Dispositional Envy Scale, Rosenberg Self-Esteem Scale, and Multi-Dimensional Scale of Perceived Social Support. The results show that self-esteem plays a partially mediating role in the association between child maltreatment and envy. In addition, sequential mediation analyses have further revealed the maltreatment effect of envy, through social support and self-esteem. Further, a multiple-group analysis has shown that men with high child maltreatment scores tend to have lower levels of social support than women. These results provide an important reference for revealing how maltreatment early in life effects social emotion in adulthood, particularly dispositional envy. They may provide a valuable resource for psychological interventions targeting people of both genders who are victims of child maltreatment.